TiO2-reduced graphene oxide-Pt nanocomposites for the photogeneration of hydrogen from ethanol liquid and gas phases - Esteves, M. Alexandra (2022)
ABSTRACT: The production of hydrogen by photocatalysis presents attractive features but also stringent requirements of materials properties. A series of TiO2-based photocatalysts containing reduced graphene oxide (rGO) and plat-inum, TiO2-rGO(x)-Pt(y) (x=0-5 wt%; y=1.5, 2.5, 3.8 wt%), were synthesized by a simple two-step procedure. The ternary composites exhibited promising performance for hydrogen generation, in both liquid and gas phase photocatalysis, using ethanol as hole scavenger, under UV light. The effect of the concentration of ethanol, graphene oxide, and Pt, as well as photocatalyst loading and solution pH were assessed. The photocatalyst TiO2-rGO3%-Pt3.8%, in the liquid phase, produced gases containing over 95% hydrogen at very high initial pro-duction rates, similar to 560 mmolh(-1)g(cat)(-1). The gas production vs irradiation time (6 h) showed linear dependence in a two-slope graph, with a drastic decrease of the rate due to Pt poisoning. Solution pH reached values of 3.5, regardless of the initial value. In the liquid phase, partial oxidation of ethanol took place with the dehydroge-nation of ethanol to acetaldehyde. In the gas phase photocatalysis, TiO2-rGO3%-Pt3.8% showed capability for photo-reforming as indicated by produced gases with a molar ratio H-2/CO2 of 3. rGO reinforces the effect of Pt as a suppressor of charge recombination.